Cancer Stem Cell and Hepatic Stellate Cells in Hepatocellular Carcinoma - Adriana G. Quiroz Reyes MSc; Sonia A. Lozano Sepulveda PhD; Natalia Martinez-Acuña PhD; Jose F. Islas PhD; Paulina Delgado Gonzalez PhD; Tania Guadalupe Heredia Torres student MSc; Jorge Roacho Perez PhD; Elsa N. Garza Treviño PhD (Technology in Cancer Research & Treatment, 2023)
Hepatocellular carcinoma (HCC) is the most common liver cancer. It is highly lethal and has high recurrence. Death among HCC patients occur mainly due to tumor progression, recurrence, metastasis, and chemoresistance. Cancer stem cells (CSCs) are cell subpopulations within the tumor that promote invasion, recurrence, metastasis, and drug resistance. Hepatic stellate cells (HSCs) are important components of the tumor microenvironment (TME) responsible for primary secretory ECM proteins during liver injury and inflammation. These cells promote fibrogenesis, infiltrate the tumor stroma, and contribute to HCC development. Interactions between HSC and CSC and their microenvironment help promote carcinogenesis through different mechanisms. This review summarizes the roles of CSCs and HSCs in establishing the TME in primary liver tumors and describes their involvement in HCC chemoresistance.